Measurement of Acetabular Component Position in Total Hip Arthroplasty in Dogs: Comparison of a Radio-Opaque Cup Position Assessment Device Using Fluoroscopy with CT Assessment and Direct Measurement - Dalbeth, Brianna N.; Karlin, William M.; Lirtzman, Ross A.; Kowaleski, Michael P. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives The aim of this study was to compare measurements of angle of lateral opening (ALO) and version determined using a radioopaque cup position assessment device imaged with fluoroscopy to measurements obtained by CT and direct measurement in a cadaveric model. Our null hypothesis was that there would not be any difference in the angles measured by the techniques.Methods Six cadavers were implanted with BFX acetabular components. The CPAD was placed and images were obtained with fluoroscopy. Measurements were obtained from the radiopaque marker bars on the CPAD device, and version and ALO were calculated. The ALO and version were determined by CT and DM. Comparisons were made using a two-way analysis of variance and a generalized linear model procedure analysis.Results There were no significant differences between the measurements for ALO (p = 0.275) or version (p = 0.226). Correlation between methods was 0.948 and 0.951 for ALO and version, respectively. The mean difference (standard deviation [SD], and 95% confidence interval [CI]) for ALO were: CT versus CPAD 1.85 degrees (± 2.32 degrees [-2.99–3.31]), CT versus DM 1.96 degrees (± 1.99 degrees [−2.2–4.27]), CPAD versus DM1.74 degrees (±2.21 degrees [−1.13 and 5.24]). The mean difference (SD [CI]) for version was CT versus CPAD 2.86 degrees (±1.56 degrees [ −2.63–1.69]), CT versus DM 1.10 degrees (±1.42 degrees [−1.57–2.09]), CPAD versus DM 1.07 degrees (±0.76 degrees [0.13–2.09]).Clinical Relevance The results demonstrate that intraoperative imaging in cadaveric specimens with the CPAD is an accurate method to determine ALO and version of the acetabular component.
Keywords: total hip arthroplasty; acetabular component; angle of lateral opening; cup position assessment device; canine cadaver